2002
DOI: 10.1143/jjap.41.7127
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Bi4Ti3O12–(Na1/2Bi1/2)TiO3Piezoelectric Ceramics

Abstract: Analysis of 24 h oesophageal pH studies can be problematic with many patients asymptomatic during the investigation, despite observations of reflux. The aim of this study was to carry out a cluster analysis of ambulatory pH studies to determine any underlying patterns and classes within the data. The results of 900 24 h pH studies were investigated using the Kohonen self-organizing feature map (SOFM), a neural network that can be used to identify clusters within multidimensional data. The clinical features wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…The piezoelectric constant d33 was directly measured by using a YE2730A d33 meter, and electromechanical coupling factors were measured by means of a resonance-antiresonance method. [15,16]. However, according to our XRD results, the bismuth layer-structured Na 0.5 Bi 4.5 Ti 4 O 15 phase can exist up to x = 99.…”
Section: Methodsmentioning
confidence: 54%
See 1 more Smart Citation
“…The piezoelectric constant d33 was directly measured by using a YE2730A d33 meter, and electromechanical coupling factors were measured by means of a resonance-antiresonance method. [15,16]. However, according to our XRD results, the bismuth layer-structured Na 0.5 Bi 4.5 Ti 4 O 15 phase can exist up to x = 99.…”
Section: Methodsmentioning
confidence: 54%
“…Many BLSF with m = 4 or 5 can also be derived from Bi 4 [8][9][10][11][12][13][14]. Recently, structural investigations on the Bi 4 Ti 3 O 12 + xNa 0.5 Bi 0.5 TiO 3 system have revealed that the bismuth layer-structured Na 0.5 Bi 4.5 Ti 4 O 15 phase and the perovskite Na 0.5 Bi 0.5 TiO 3 phase are prone to reject each other in their solid solution [15,16]. However, little data on the * Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…6 On increasing the number of perovskite layers ͑n͒, the microstructural, magnetic, and physical properties of the materials can be altered significantly. [7][8][9][10][11][12][13][14][15] Chemical doping of perovskite type materials, without producing a large decrease in their Curie temperature ͑T c ͒, has been useful in enhancing their electrical and magnetic properties. 9,[16][17][18][19][20] Mn 3+ doping has been reported to be effective for suppressing leakage current and improving the polarization switching properties of Bi 4 Ti 3 O 12 single crystals.…”
Section: Introductionmentioning
confidence: 99%
“…The crystal structure of chemical formula Na 0.5 Bi 4.5 Ti 4 O 15 can be expressed as one perovskite block Na 0.5 Bi 0.5 TiO 3 (NBT) inserted hypothetically between two bismuth layers of BT. With three pseudo-perovskite blocks Bi 2/3 1/3 TiO 3 (B T, where denotes cation vacancy) of BT [18], two types of pseudo-perovskite blocks are formed in NBT4 lattice. With the proposed mechanism of layer-by-layer intercalation by defects sweeping across grain [8], the transformation from BT to NBT4 has been verified by at the temperature exceeding 800 • C. A complex sequence of phase transitions of two type perovskite blocks may be traced in Fig.…”
Section: Resultsmentioning
confidence: 99%